2002
DOI: 10.1182/blood-2001-12-0340
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of FcεRI-mediated degranulation by an adaptor protein 3BP2 in rat basophilic leukemia RBL-2H3 cells

Abstract: IntroductionAggregation of the high-affinity IgE receptor (Fc⑀RI) on mast cells mediates the allergic response by the release of inflammatory mediators by degranulation and production of cytokines and arachidonic acid metabolites. 1 Fc⑀RI signals by activating nonreceptor-family proteintyrosine kinases (PTKs) Lyn, Syk, and Btk. On aggregation of Fc⑀RI␣ subunits, the Src family PTK Lyn phosphorylates the associated Fc⑀RI␤ and ␥ subunits on tyrosine residues in the immunoreceptor tyrosinebased activating motif. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
89
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(93 citation statements)
references
References 24 publications
1
89
0
3
Order By: Relevance
“…An in vitro binding study suggested that phosphorylation of Tyr 183 of 3BP2 could be associated with Vav and phospholipase C-␥ (4). In mast cells, overexpression of the 3BP2-SH2 domain suppressed high affinity IgE receptor (Fc⑀RI)-mediated tyrosine phosphorylation of phospholipase C-␥, Ca 2ϩ mobilization, and degranulation (5). These findings have demonstrated that 3BP2 plays a critical role in hematopoietic cells.…”
mentioning
confidence: 69%
“…An in vitro binding study suggested that phosphorylation of Tyr 183 of 3BP2 could be associated with Vav and phospholipase C-␥ (4). In mast cells, overexpression of the 3BP2-SH2 domain suppressed high affinity IgE receptor (Fc⑀RI)-mediated tyrosine phosphorylation of phospholipase C-␥, Ca 2ϩ mobilization, and degranulation (5). These findings have demonstrated that 3BP2 plays a critical role in hematopoietic cells.…”
mentioning
confidence: 69%
“…Reports indicated that some downstream signaling events of FcRI may be involved in antigen-induced action of mast cells which lead to cytokine expression including (17,18). To investigate the specificity of Gab2 siRNA on degranulation, we also investigated whether Gab2 siRNA could suppress the release of -hexosaminidase through the Ca 2+ -dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Cependant, les données publiées, fondées sur des approches de type gain ou perte de fonction, indiquent que 3BP2 joue un rôle régulateur dans la signalisation des immunorécepteurs dépendante des kinases Src et Syk (Figure 2). Ainsi, 3BP2 a été impliquée dans la stimulation par le récepteur FcγRIII de la cytotoxicité des cellules NK [11], la dégranulation induite par l'aggrégation des récepteurs FcεRI [10], ou encore l'activation, par les récepteurs de l'antigène de cellules T (TCR) et B (BCR), de NFAT et AP-1, deux facteurs transcriptionnels essentiels à l'homéostasie des leucocytes [4,12]. Dans ce contexte, une fonction probable de 3BP2 est à rechercher dans une cascade de signalisation dépen-dante de la PLC-γ, régulant le métabolisme lipidique et calcique des leucocytes stimulés par les immunoré-cepteurs.…”
Section: Bp2 : Structure Et Partenaires Moléculairesunclassified
“…La surexpression de 3BP2 dans la lignée T Jurkat induit une augmentation considérable des activités NFAT/AP-1 stimulées par le TCR, par une voie dépendante de la petite GTPase Ras et de la calcineurine, une sérine/thréonine phosphatase activée par le calcium et cible de la cyclosporine A [4,12]. Dans une lignée de cellules basophiles, la surexpression d'une forme dominante négative de 3BP2 réduit fortement la phosphorylation de PLC-γ1/2, l'augmentation de calcium intracytoplasmique et la dégranulation induite par le FcεRI [10]. Des approches de type perte de fonction, incluant la suppression de l'expression de 3BP2 par des petits ARN interférants et l'expression d'une forme dominante négative, soulignent encore l'importance de 3BP2 pour l'activation du facteur nucléaire NFAT par le TCR et le BCR [6,12].…”
Section: Bp2 : Structure Et Partenaires Moléculairesunclassified
See 1 more Smart Citation